Հայաստանում քաղաքացիական հասարակության մոդելի ձևավորման խնդիրը էթնոմշակութային համատեքստում - Ն. Մ. Գալստյան (ՀՀ ԳԱԱ հրատ.)
Анализ развития и становления гражданского общества в Армении на основе мирового опыта, демократии и поликультурных процессов предполагает разработку новых методологических подходов с учетом особенностей исторического развития армянской цивилизации. Изучение опыта исторического развития различных стран указывает на то, что в мире нет единой модели построения гражданского общества. The analysis of the problem of civil society development and establishment in Armenia assumes elaboration of new methodological approaches in present global experience, democracy and multicultural ambient conditions taking into consideration the peculiarities of historical development of Armenian civilization. The study of the practice of historical development in different countries reveals that there is no a universal model in the world for building a civil society, which, based on social-cultural events, has different content, structure and subjects involving level.
Keywords: H Social Sciences; Sociology